Evaluación de la condición fisiológica de la almeja Polymesoda caroliniana (Bivalva: Corbiculidae) expuesta a cadmio - Vázquez Castro, José Ángel (Universidad Autónoma Metropolitana, 2019)
In environmental monitoring, the qualitative evaluation of histological alterations has been proposed as a biomarker to evaluate the effects of contamination in aquatic organisms. However, quantitative analysis tools that allow the determination of the health of wild or experimental organisms are not considered. The aim was to calculate the health index of clams Polymesoda caroliniana exposed to 300 µg/L of cadmium (in devices with sediment and without sediment) through the quantitative analysis of tissue alterations. 80 preparations of gonad and digestive gland stained with H-E were analyzed. The pathological alterations were characterized and a prevalence matrix was constructed. Each alteration was assigned a pathological importance factor (1 to 3) and an ascending value according to the dissemination of the alteration. Data were statistically analyzed with the Student´s T test (when the data presented normality and homoscedasticity) and Mann-Whitney U test (when the data did not present normality or homoscedasticity) to evaluate the differences between the control and experimental organisms. The observed alterations in organisms exposed to cadmium were: brown cells, atrophies, eosinophilic secretions in the digestive gland; only spherical inclusions were observed in the gonad. The alterations observed are type 2 (moderate reversible) and the highest health index was in the gonad of 0.6, which means that it had greater damage with respect to the digestive gland. The use of categories of histopathological evaluation in other organs is recommended to establish a general health index in organisms exposed to cadmium, which will allow inferring the effects of cadmium in wild organisms.; En el monitoreo ambiental, se propone la evaluación cualitativa de alteraciones histológicas como biomarcador para evaluar los efectos de la contaminación en organismos acuáticos. Sin embargo, no se consideran herramientas de análisis cuantitativas que permitan determinar la salud de los organismos silvestres o experimentales. El objetivo del trabajo fue calcular el índice histopatológico de salud de almejas Polymesoda caroliniana expuestas a 300 µg/L de cadmio (en dispositivos con sedimento y sin sedimento) a través del análisis cuantitativo de alteraciones tisulares. Se analizaron 80 preparaciones de gónada y glándula digestiva teñidas con H-E. Se caracterizaron las alteraciones patológicas y se construyó una matriz de prevalencia. A cada alteración se le asignó un factor de importancia patológica (1 a 3) y un valor ascendente según la diseminación de la alteración. Los datos fueron tratados estadísticamente a través de la prueba de student´s T (cuando los datos presentaron normalidad y homocedasticidad) y U-Mann Whitney (cuando los datos no presentaron normalidad u homosedasticidad) para evaluar las diferencias entre los organismos control y experimentales. Las alteraciones observadas en organismos expuestos a cadmio fueron: células cafés, atrofias, secreciones eosinófilas en glándula digestiva; en gónada sólo se observaron inclusiones esféricas. Las alteraciones observadas son de tipo 2 (moderado reversible) y el índice de salud en la gónada fue de 0.6, lo que significa que este órgano tuvo mayor daño con respecto a la glándula digestiva. Se recomienda el uso de categorías de evaluación histopatológica en otros órganos para establecer un índice de salud general en organismos expuestos a cadmio, que permitan inferir los efectos del cadmio en organismos silvestres.